A Pre-implementation Study of Volumetric Modulated Arc Therapy for Same-day Planning and Treatment of Vertebral Bone Metastases Within a Rapid-access Palliative Radiotherapy Programme. Issue 10 (October 2021) - Dennis, K.; Linden, K.; Zohr, R.; McGrath, C.; MacPherson, M.; Renaud, J.; Granville, D.; Gaudet, M.; Ali, E.
Abstract: Aims: We aimed to develop a process for same-day contouring, planning, quality assurance and delivery of volumetric modulated arc therapy (VMAT) for vertebral bone metastases within our institution's rapid-access palliative radiotherapy programme. Materials and methods: Two thoracic (T6–7, T3–7) and two lumbar (L2–3, L1–5) targets were contoured on computed tomography images acquired from an anthropomorphic phantom and five patient scans. Inverse planning aimed to provide coverage of a prescribed dose of 8 Gy with a combined lung V2Gy < 25% and a combined kidney mean dose <2 Gy. Serial plans were created to identify an efficient combination of six main planning variables specific to our treatment planning system: (i) voxel size (3 mm versus 5 mm), (ii) Monte Carlo statistical uncertainty (1% per calculation versus 3% per control point), (iii) fluence smoothing (medium versus high), (iv) number of iterations of segment shape changes during optimisation (1 versus 5), (v) dose calculation algorithm (Monte Carlo versus pencil beam) and (vi) number of arcs (single versus multiple). Contouring, planning, quality assurance and treatment delivery were timed. Results: The combination of planning variables deemed efficient and appropriate was: a 3 mm voxel size, statistical uncertainty of 1% per calculation, medium fluence smoothing, five iterations of segment shape changes, Monte Carlo dose calculation and single full arc delivery. Patient scan contouring times ranged from 7 to 9 min (T6–7), 11–13 min (T3–7), 5–7 min (L2–3) and 8–10 min (L1–5) and planning times ranged from 9 to 15 min (T6–7), 13–25 min (T3–7), 18–25 min (L2–3) and 21–31 min (L1–5). Physics quality assurance times ranged from 15 to 21 min and beam-on times ranged from 3 to 6 min. Conclusions: The combined elements of VMAT for thoracic and lumbar vertebral bone metastases were completed in under 2 h. This new process makes same-day contouring, planning, quality assurance and treatment delivery of VMAT feasible within our rapid-access palliative radiotherapy programme. Highlights: We studied volumetric modulated arc therapy (VMAT) for vertebral metastases. VMAT is difficult to plan and deliver in same-day rapid access palliative programmes. Our process enables same-day contouring, planning, quality assurance and delivery. All components were completed in less than 2 h. Same-day VMAT for vertebral metastases appears feasible in our rapid-access programme.